ANALISIS PROSES PEMBELAJARAN MELALUI LESSON STUDY FOR LEARNING COMMUNITY BERBASIS TRANSKRIP BASED LEARNING ANALYSIS (TBLA) - Veny Agustini Prianggita; Hendayana, Sumar; Jihaduddin; Riswanto, Dody (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2022)
Lesson Study for Learning Community (LSLC) activities have the potential to encourage many parties to do their best in improving the quality of learning. LSLC activities based on Transcript Based Learning Analysis (TBLA) are a way to enable teachers to sharpen their learning lenses intensively and comprehensively from various perspectives. The problems studied were "how is the learning process through TBLA-based LSLC" and "what are the results of the analysis of the learning process for Student Center Learning (SCL) or Teacher Center Learning (TCL)?". The objectives of this research are: 1. To produce an analysis of the learning process whether learning activities are in the form of SCL or TCL learning based on TBLA through LSLC, 2. To help teachers and schools to improve the quality of learning. The method used is Action Research which includes the stages of Plan-Do-See-Making Transcripts-Analyzing. The instrument used is Lesson Study using learning transcripts. The data analysis technique used is descriptive analysis. The results of this study are: (1). Planning has taken place by making Lesson Design together, opening classes for observation, and holding warm reflections, 2. Based on the results of the Analytical Transcript, it shows that the learning process is still dominated by the teacher (TCL) who tends to confirm student answers and repeat students' answers.